NARRATIVE REVIEW: INCIDENCE, CAUSES AND INTERVENTION STRATEGIES OF MEDICATION ERRORS TO IMPROVE CHEMOTHERAPY SERVICES IN HOSPITALS - Nurliyani, Hani; Alfian, Sofa Dewi; Rahayu, Cherry; Pradipta, Ivan Surya (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Medication errors (MEs) are medication errors that have the potential to harm patients during treatment or care. Cancer care is a complex and interconnected system and many errors can be catastrophic. ME in antineoplastic drugs have the potential to cause permanent injury and even death. Evaluation measures of ME incidence in Indonesia are still not optimally carried out, thus leading to the need for a good understanding of the potential ME incidence, especially in cancer patient care. A good understanding of the incidence of medication errors will encourage preventive efforts against the potential occurrence of ME. This narrative review aims to provide information related to the incidence of ME in the Chemotherapy department at the hospital, the causative factors, and the handling and prevention efforts. Scientific information searches were conducted on the PubMed and Google Scholar databases for the period 2012-2022. The results showed that the incidence of ME mostly occurred in the prescription phase, namely in the form of dosage errors (45–59.3%), incomplete prescriptions (43–45.5%), drug frequency errors (30.4%), and     errors in patient name, age, and diagnosis data (22.5%). Several aspects contributing to the occurrence of ME were identified, including work procedures, staff, organizational systems, and staff understanding of medication regimens. This study concluded that there is a need to regulate and evaluate several aspects, including work procedures, availability of auxiliary systems, and increasing the capacity of human resources involved. This may prevent the occurrence of ME.